In-Service Training Framework for Industrial Relations And Training Officer at Malaysian Vocational College - Ramli Sappar; Mohammad Hussain, Mohd Azlan; Rafeizah Mohd Zulkifli; Kamalularifin Subari; Mohd Firdaus Mustaffa Kamal (Journal of Technical Education and Training, 2024)
A collaborative relationship between vocational colleges and the industry sector is essential to provide highly skilled graduates that align with the industry’s current demands. The critical need for the implementation of industrial collaboration in vocational colleges has given rise to polemics about the ability and expertise of industrial relations and training officers (KUPLI) in managing the implementation of effective industrial collaborative relations. This study was conducted to explore issues in the implementation of industrial collaborative relationships as well as to explore the need for the implementation of effective industrial collaborative relationships based on KUPLI’s perspective. This study is conducted using a qualitative approach, while the design of this study is in the form of a multiple-embedded case study. The implementation of this study is essential in helping every party interested in implementing industrial collaborative relations in improving the role of KUPLI to succeed in effective industrial collaborative relations. The findings of the study found that there are six critical issues and requirements for the implementation of effective industrial collaborative relations in Malaysian vocational colleges, among which are the issue of unclear collaborative direction, training management issues, the need for effective interaction and the need for a comprehensive support system.